SEJARAH KESENIAN JARAN KEPANG DI KECAMATAN RENGAT (2001-2019) - Mulwalto Mulwalto; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Indonesia is very rich in culture that encompasses different aspects of life. One of the cultures that the Indonesian people possess is traditional art. Each region certainly has different traditional arts that become its own characteristics. One form of culture is art. Javanese art owned by our land is the art of the braided jaran. In East Java, jaran braids were originally not a performing art, but part of a ritual. This dance is very popular in the community, especially the people of the Rengat District. Lots of people rave about watching this braid jaran show. The purpose of writing in this study is to determine the background of the entry of Jaran Kepang art into Rengat, its performance process, its function, and its differences from Jaran Kepang art in East Java. The research methodology used in this research is the historical method. Jaran Kepang art started to appear in Rengat district in 1960. Explain about the development of jaran kepang art in the Rengat district from 2001-2019. In the implementation part of the show, before the show starts, the players first prepare the items and tools that will be used during the show. When the preparations are complete, proceed to the opening. One type of dance is performed in one phase. The dances that are usually performed include flashlight, bendrong, buto barong, hanoman, buto lawas, sintren and badutan. The art of jaran braiding has a function as a means of cultural preservation, but also as a means of ritual, as a personal entertainment and as an aesthetic presentation. The differences that exist in the art of jaran wickerwork in Rengat district and that in East Java can be seen in the rituals performed by the pawang at the opening of the performance event, from the aspect of the dance stage to the final part.Key Words: History, Jaran Kepang Art, Rengat District